Analysis of Students’ Mathematical Semiotic Representation Ability in Terms of Self-Confidence - Bella Putrie Andriani; Depi Setialesmana; Linda Herawati (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Mathematical semiotic representation ability plays an important role in helping students understand and solve mathematical problems. However, differences in students' self-confidence may influence how they construct mathematical representations. This study aimed to analyze students' mathematical semiotic representation abilities in terms of high, medium, and low levels of self-confidence. This research employed a descriptive qualitative approach involving eighth-grade students of SMP Negeri 19 Tasikmalaya. Three students representing high, medium, and low levels of self-confidence were purposively selected based on the results of the self-confidence questionnaire, the mathematical semiotic representation ability test, and semi-structured interviews. The research instruments consisted of a self-confidence questionnaire and a mathematical semiotic representation ability test developed based on Peirce's semiotic indicators, namely iconic (visual representation), symbolic (the use of mathematical symbols and formulas), and indexical (explaining the relationship between the solution and the problem context). Data were collected through self-confidence questionnaires, written tests, and semi-structured interviews, then analyzed through data reduction, data display, and conclusion drawing. The findings showed that the student with high self-confidence was able to represent problem situations through appropriate visual representations (iconic), use mathematical symbols and formulas correctly to solve the problem (symbolic), and explain the relationship between the solution and the problem context logically (indexical). The student with medium self-confidence also demonstrated all three indicators but showed inaccuracies in calculations and hesitation when explaining the obtained results. Meanwhile, the student with low self-confidence was able to construct visual and symbolic representations but experienced difficulties in explaining the relationship between the obtained solution and the context of the problem, indicating that the indexical representation was not fully achieved.